Developing new laser sintering materials for snowboarding applications - Vasquez, M.; Cross, J.; Hopkinson, N.; Haworth, B. (Procedia Engineering, 2012)
Over the past two decades Additive Manufacturing has radically shifted the way that many sports companies design new products. Burton Snowboards is one of these companies. They utilize a technology called laser sintering to streamline the prototyping process for many of their rigid snowboard binding products. Laser sintering is a manufacturing technology that takes digital files and constructs parts in three dimensions by depositing and consolidating layers of material using a laser. Currently, one of its biggest limitations is the restricted range of polymer materials that are available. The most common polymer materials used in laser sintering are Nylon-12 or Nylon-11. While these materials allow for the creation of robust rigid functional prototypes like snowboard binding baseplates or high backs, their ductility and elasticity is limited. The Burton product line includes many parts that demand more flexibility, especially for cold weather application such as straps, padding, or footwear components. This paper will discuss a scientific research collaboration between Loughborough University and Burton Snowboards to identify, characterize, develop, and test a new elastomer laser sintering material. Polymer characterization tests were completed at Loughborough University and laser sintering processing trials were performed at Burton Snowboard's Rapid Prototype laboratory. This targeted development process has implications beyond snowboarding and could be applied to other areas of the sporting goods industry where flexible materials are required, including footwear or personal protective equipment.